2018
DOI: 10.5194/amt-11-5549-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cloud fraction determined by thermal infrared and visible all-sky cameras

Abstract: Abstract. The thermal infrared cloud camera (IRCCAM) is a prototype instrument that determines cloud fraction continuously during daytime and night-time using measurements of the absolute thermal sky radiance distributions in the 8–14 µm wavelength range in conjunction with clear-sky radiative transfer modelling. Over a time period of 2 years, the fractional cloud coverage obtained by the IRCCAM is compared with two commercial cameras (Mobotix Q24M and Schreder VIS-J1006) sensitive in the visible spectrum, as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…A further refinement is the use of an infrared sky camera which allows cloud cover to be determined during the night. A research prototype, the thermal infrared cloud camera (IRCCAM), has been continuously operating at DAV since September 2015 (Aebi et al, 2018). A comparison of IRCCAM with the visible sky cameras gave FCC values to within ±0.07 and to within ±0.05 for APCADA.…”
Section: Improvement Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further refinement is the use of an infrared sky camera which allows cloud cover to be determined during the night. A research prototype, the thermal infrared cloud camera (IRCCAM), has been continuously operating at DAV since September 2015 (Aebi et al, 2018). A comparison of IRCCAM with the visible sky cameras gave FCC values to within ±0.07 and to within ±0.05 for APCADA.…”
Section: Improvement Of Methodsmentioning
confidence: 99%
“…A comparison of IRCCAM with the visible sky cameras gave FCC values to within ±0.07 and to within ±0.05 for APCADA. Aebi et al (2018) concluded that the use of FCC from infrared sky cameras could increase the accuracy of cloud-free climatologies when FCC time series 25 of adequate length become available.…”
Section: Improvement Of Methodsmentioning
confidence: 99%
“…With the development of hardware technologies such as charge-coupled devices and digital image processing, many ground-based full-sky cloud-measuring instruments have been successfully developed. Currently, the most representative instruments include the Whole Sky Imager (WSI; Johnson et al, 1989), Total Sky Imager (TSI; Long and Deluisi, 1998;Long et al, 2006), Infrared Cloud Imager (ICI; Shaw et al, 2005;Thurairajah and Shaw, 2005;Nugent et al, 2009Nugent et al, , 2013, All Sky Imager (ASI; Cazorla et al, 2008), Whole Sky Infrared Cloud Measuring System (WSIRCMS; Sun et al, 2008), Total Sky Cloud Imager (TCI; Yang et al, 2012), All-Sky Infrared Visible Analyzer (ASIVA; Klebe et al, 2014), Whole Sky Camera (WSC; Kuji et al, 2018), and All Sky Camera (ASC; Aebi et al, 2018). The above instruments provide hardware support for analyzing ground-based cloud images, making the automated observation of groundbased cloud images possible.…”
Section: Introductionmentioning
confidence: 99%
“…Ghonima et al (2012) compared the pixel red-blue ratio (RBR) to the RBR of a clear-sky library (CSL) for more accurate cloud segmentation. Different from the various algorithms mentioned above, Calbo and Sabburg (2008) presented several features that are computed from the threshold image, extracted from statistical measurements of image texture, based on the Fourier transform of the image, and can be useful for cloud segmentation of all-sky images. Peng et al (2015) designed a classifier-based pipeline of identifying and tracking clouds in three-dimensional space to utilize all three totalsky imagers for multisource image correction to enhance the overall accuracy of cloud detection.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Aebi et al (2018), there are some uncertainties with the automatic detection of thin high-level clouds. Therefore, for the final data set of 206 measurements, only situations with a measured CBH of at least 5 km are considered.…”
Section: Case Selectionmentioning
confidence: 99%